2019
DOI: 10.1371/journal.pone.0204636
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of neurocognitive disorders observed among adult people living with HIV/AIDS in Southern Ethiopia: A cross-sectional study

Abstract: BackgroundComprehensive care given to people living with HIV/AIDS is improving over time; however, their concurrent cognitive illness is still ignored, under screened and treated particularly in developing countries. And this problem is also striking in Ethiopia. Therefore, the objective of this study was to assess HIV-associated neurocognitive disorders and associated factors among adult people living with HIV/AIDS.MethodsAn institution based cross sectional study was conducted from April to May, 2017 at Gamo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 64 publications
6
51
2
Order By: Relevance
“…Similar findings were found in a South African study that reported HIV-infected children with a median age of 5 years did not show improvement in neurocognitive function after 6 months of ART (24). In addition, the finding from the present study is consistent with studies showing that children infected with HIV relative to uninfected groups evidence focal neurocognitive deficits on task that measures working memory (25); processing speed (26); visual motor integration, sustained attention (27); and motor speed coordination (28). Unlike in the present study, these studies did not find impairment on global intellectual functioning.…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were found in a South African study that reported HIV-infected children with a median age of 5 years did not show improvement in neurocognitive function after 6 months of ART (24). In addition, the finding from the present study is consistent with studies showing that children infected with HIV relative to uninfected groups evidence focal neurocognitive deficits on task that measures working memory (25); processing speed (26); visual motor integration, sustained attention (27); and motor speed coordination (28). Unlike in the present study, these studies did not find impairment on global intellectual functioning.…”
Section: Discussionsupporting
confidence: 91%
“…The point prevalence of the neurocognitive de cit in this study was 41%. The present prevalence ndings were similar to those of a study from Canada (39.4%)(26) but higher when compared to other studies from Ethiopia (33.3%,67.1%) (21,27), sub-Saharan Africa (30.9%) (28). However, the present ndings were less than some of the studies conducted in Nigeria (54.3%, 2012; 66.2%, 2013) (29,30), Cameroon (85%) (31), Asia (85%) (32) and Uganda (64.4%, 2013) (33).…”
Section: Factors Associated With the Neurocognitive De Cit: A Multivasupporting
confidence: 89%
“…Gender, education, marital status, current CD4 count and hospital stay were included in the model based on previous studies showing them to be consistent predictors for HAND (18)(19)(20)(21)(22)(23)(24)(25). The logistic regression model was statistically signi cant, χ2(9) = 72.91.…”
Section: Factors Associated With the Neurocognitive De Cit: A Multivamentioning
confidence: 99%
“…Gender, education, marital status, current CD4 count and hospital stay were included in the model based on previous studies showing them to be consistent predictors for neurocognitive impairment. [25][26][27][28][29][30][31][32] The logistic regression model was statistically significant, χ2 (9) = 72.91. The model explained 35.0% (Nagelkerke R 2 ) of the variance in neurocognitive impairment status and correctly classified 75.8% of cases.…”
Section: Factors Associated With the Neurocognitive Impairment: A Mulmentioning
confidence: 91%